Analisis Pengaruh Jumlah Uang Beredar (Jub), Pembiayaan Mudharabah (Pm) Dan Zakat, Infak, Sedekah (Zis) Terhadap Pertumbuhan Ekonomi Di Indonesia Periode 2007 - 2014 - Suci Anggraeny, Andita; Eni Setyowati,, Eni Setyowati,SE, M.Si (2017)
This research purposed to analyze the influence of the Money Supply (JUB), Mudharaba Financing (PM), and Zakah, Infak and Alms (ZIS) on Economic Growth in Indonesia Period 2007-2014. This research was using three monthly data and that are secondary data. Data analysis techniques used in this research is Linear Regression Multiple Method. Based on data analysis in this study can be concluded that variable of Money Supply (JUB), Mudharaba Financing (PM), and Zakah, Infak and Alms (ZIS) have possitive influence on Economic Growth, and that variables have contribution on Economic Growth too. Keywords : Gross Domestic Product (GDP), Money Supply (JUB), Mudharaba Financing (PM), Zakah Infak and Alms (ZIS), and Liniear Regression Multiple Method.